American rhapsodies revisited: figures de l'altérité et voix mêlées dans Music through the Floor (2005) d'Eric Puchner - Nathalie Vincent-Arnaud (Anglophonia)
The collection of short stories Music through the Floor, published in 2005, is Eric Puchner's first fictional work. In the wake of some of his famous predecessors such as Cheever or Carver who have deeply influenced his writing, Puchner gets to grips with the closely related notions of diversity, otherness and alienation which lie at the core of his characters' concerns with identity and response to their social and linguistic environment. As suggested by the title itself, music stands as the overriding metaphor for the conflicting identities, peculiarities and human relationships staged by the short stories in many different ways, just as music actually performed is a major element through which various voices can be heard. In keeping with some famous works of art–mainly musical or cinematographic–aimed at characterizing the U.S.A. as a whole, Puchner's writing gives birth to a rhapsodic form in which, even though they do blend sometimes in an elusive way, each voice is that of a soloist performing on his own in a "community of loners".